Malaysian youth and environmental sustainability: a review - Abdul Rahman, Haliza (UPSI Press, 2020)
Climate change, deforestation, land degradation, and pollution are some of the environmental concerns that threaten the health of the planet, humans, and other living things. The youth will have to live with the adverse effects of these environmental threats and will be decision-makers in the future. As a result, they have to be actively involved in environmental issues to ensure ecological sustainability, which has become a national and global priority. In Malaysia, youth make up 45.8% of the total population and are emerging change agents in driving the economic change of the country. Thus, this article examines whether youths in Malaysia have a high awareness of the environment and a positive environmental attitude. They need to have a high level of environmental awareness and participation, where people are placed at the forefront of environmental sustainability initiatives. For methodology, this paper used the qualitative method by analysing and reviewing journal articles, reports, newspaper publications, and other relevant documents. The findings show that Malaysian youth generally have a high level of environmental awareness and generally positive environmental attitudes. However, their level of environmental participation issues seems inadequate. The paper also highlights current youth-based programs implemented by government and non-governmental organizations to involve youth in the environment and proposes strategies to enhance their involvement. This literature review is beneficial to environmentalists, academicians, and environment-based organizations, and government institutions.